New insights into the phylogenetic relationships among wild onions (Allium, Amaryllidaceae), with special emphasis on the subgenera Anguinum and Rhizirideum, as revealed by plastomes - Yang, JiYoung; Kim, Seon-Hee; Gil, Hee-Young; Choi, Hyeok-Jae; Kim, Seung-Chul (Frontiers in Plant Science, 2023)
The genus Allium, with over 900 species, is one of the largest monocotyledonous genera and is widely accepted with 15 recognized subgenera and 72 sections. A robust subgeneric and sectional relationships within Allium have long not been resolved. Based on 76 species of Allium (a total of 84 accessions), we developed a highly resolved plastome phylogenetic framework by integrating 18 newly sequenced species (20 accessions) in this study and assessed their subgeneric and sectional relationships, with special emphasis on the two subgenera Anguinum and Rhizirideum. We retrieved the three major evolutionary lines within Allium and found that the two subgenera Anguinum and Rhizirideum are monophyletic, whilst others are highly polyphyletic (e.g., Allium, Cepa, Polyprason, and Melanocrommyum). Within the subgenus Anguinum, two strongly supported sublineages in East Asian and Eurasian-American were found. Allium tricoccum in North America belonged to the Eurasian clade. The distinct taxonomic status of A. ulleungense and its sister taxon were further determined. In subg. Rhizirideum, the Ulleung Island endemic A. dumebuchum, shared its most recent common ancestor with the species from Mongolia and the narrow Korean endemic A. minus. Two Ulleung Island endemics were estimated to originate independently during the Pleistocene. In addition, a separate monotypic sectional treatment of the east Asian A. macrostemon (subg. Allium) and sister relationship between A. condensatum and A. chinense was suggested.